Effects of Food on Acne Vulgaris - Marelda I. C. Wilar; Marlyn G. Kapantow; Pieter L. Suling (Universitas Sam Ratulangi, 2022)
Abstract: Acne vulgaris is one of the skin problems characterized by chronic inflammation of pilosebaceous follicles which leads to the present of pleomorphic array of lesions, consisting of comedones, papules, pustules, nodules, cysts with varying extent and severity, which may associated by pain and itchiness. This study aimed to identify the effects of dietary intake on acne vulgaris. This was a literature review study using three databases namely Pubmed, Google Scholar, and British Journal of Dermatology. The results obtained 10 articles that met the inclusion and exclusion criteria. Foods with high glycemic load, high in fat, milk, cheese, yoghurt, candies, cakes, ice cream, and alcohol could exacerbate acne vulgaris. Consuming fish, fruits, and vegetables was protective against acne vulgaris. In conclusion, certain foods affect the development of acne vulgaris.Keywords: acne vulgaris; dietÂ Abstrak: Akne vulgaris merupakan salah satu masalah kulit yang ditandai dengan adanya peradangan kronis pada folikel pilosebasea sehingga muncul lesi polimorfik dengan tingkat dan keparahan bervariasi seperti komedo, papul, pustul, nodus, kista, yang dapat disertai nyeri dan gatal. Penelitian ini bertujuan untuk mengetahui pengaruh makanan terhadap akne vulgaris. Penelitian ini berbentuk suatu literature review yang menggunakan database Pubmed, Google Scholar, dan British Journal of Dermatology. Hasil penelitian mendapatkan 10 artikel yang sesuai dengan kriteria inklusi dan eksklusi. Makanan dengan indeks glikemik tinggi, tinggi lemak, susu, keju, yogurt, permen, kue, es krim, cokelat, dan alkohol dapat memperburuk perkembangan akne vulgaris. Mengonsumsi ikan, buah, dan sayur merupakan faktor protektif dari akne vulgaris. Simpulan penelitian ini ialah makanan tertentu memengaruhi perkembangan akne vulgaris.Kata kunci: akne vulgaris; makanan